Compact h‐ring antenna with dual‐band operation for wireless sensors and RFID tag systems in ISM frequency bands. Issue 4 (27th February 2013) - Ojaroudi, Nasser; Ojaroudi, Mohammad
Abstract A novel design of dual‐band microstrip‐fed monopole antenna for radio frequency identification (RFID) applications is presented in this article.The proposed antenna is designed to operate at 2.45 GHz, 5.8 GHz (ISM bands), and it is fabricated on the FR4 substrate with dielectric constant of 4.4. By using H‐shaped antenna, we can gave a new resonance at lower frequencies (2.45 GHz), also by embedding H‐shaped slot, the proposed antenna with H‐ring structure can be created and achieves good dual‐band operation. The measured impedance bandwidth for −l0 dB return loss is from 2.05 to 2.83 GHz (33%) and 5.30 to 6.32 GHz (15.0%), covering the 2.4/5.8 GHz RFID operating bands. Simulated and experimental results obtained for this antenna show that the proposed H‐ring monopole antenna has a good antenna gains and radiation behavior within the 2.4/5.8 GHz frequencies. The designed antenna has a small size of 12 × 18 mm2. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:697–700, 2013; View this article online at wileyonlinelibrary.com. DOI: 10.1002/mop.27404